Proposing an Integrated Islamic Microfinance Model in Alleviating Poverty and Improving the Performance of Microenterprises in Indonesia - Hawariyuni, Weni; Hj. Kassim, Salina (Journal of Accounting Research, Organization and Economics, 2019)
Objective This study proposes an integrated Islamic microfinance model in alleviating poverty and improving the performance of microenterprises based on a case study of Indonesia, by focusing specifically on BRI Microbanking.Design/methodology This study adopts the exploratory study to construct the integrated Islamic microfinance with the purpose to alleviate poverty and enhance the business performance of enterprises.Results As Islamic microfinance is known widely due to the high demand from Muslim countries. Since, it plays a crucial role effectively in alleviating poverty and developing the business performance on enterprises, particularly on microenterprises. Presently, many scholars attempted to build a successful Islamic microfinance model by using Islamic financing instruments such as mudarabah, musyarakah, and murabahah. This study attempts to build an integrated Islamic microfinance model by using BRI Syariah Micro as a case study. It is expected that this integrated Islamic microfinance model can enrich existing models in terms of social and economic aspects.Originality/Value This research concentrates on proposing an integrated Islamic microfinance model based on the case study of BRI Syariah Microbanking. There seems to be a gap in the literature on the actual implementation of integrated Islamic microfinance in the world. The study highlights major factors to be emphasized to ensure the effectiveness of proposing an integrated Islamic microfinance model for BRI Syariah micro banking to alleviate poverty and to improve the performance of microenterprises.